Risk Factors Analysis of Diabetes Prevalence in Wetland Area: A Study from Borneo Wetland Study on Diabetes - Nanang Miftah Fajari; Felix Hariyanto; Hendra Nur'amin; Nuvita Hasrianti (Clinical and Research Journal in Internal Medicine)
Background: National Basic Health Survey held by the Ministry of Health Republic of Indonesia shows the prevalence of Diabetes Mellitus increased from 6.9% to 8.5% in 2018. Wetland is an area covered by shallow water on the surface, which represents a unique ecosystem.